Study on the performance of pervious concrete under freeze–thaw cycle based on PFC3D - Xiao, Qidan; Gao, Bo; Deng, Hui; Zhao, Jun (Frontiers in Physics, 2025)
Pervious concrete exhibits different freeze–thaw performance compared to conventional concrete owing to its unique porous structure. Therefore, studying its mechanical and durability properties under freeze–thaw conditions has become a pressing issue. A numerical model of pervious concrete was created using the discrete element method based on actual aggregates to evaluate the impact of freeze–thaw cycles (FTCs) on the mechanical properties of pervious concrete. Pore water in the microstructure of pervious concrete was defined using PFC3D software through simulation of the freezing and expansion processes of the pore water, while applying freeze–thaw loading. This study employs the parallel bond model in PFC3D software to account for adhesion between the material particles. The linear ontological relationship of the parallel bond model was modified to a linear curvilinear relationship. The FTCs resulted in strength loss reductions of 0.62%, 2.17%, 4.06%, and 5.87% for corresponding mass losses of 0.66%, 0.89%, 1.21%, and 6.66% compared to the control. The models were monitored for fracture location and uniaxial compressive damage using PFC3D software, and the attenuation constant of the freeze–thaw resistance of pervious concrete was examined with respect to varying porosity and initial uniaxial compressive strength (UCS). The results indicate that the decay constant increases with increasing porosity and modulus of elasticity while decreasing with increasing values of the initial UCS.